Polygala longifolia Poir. (Polygalaceae, Fabales), the first record in the flora of Bhutan - Tobgay, Sonam; Wanghchuck, Karma; Nidup, Tshering (Biodiversity: Research and Conservation, 2024)
We report Polygala longifolia Poir. as a new record, confirming that it is a component of the flora of Bhutan. The specimen was observed thriving on dry slopes in Chir pine forest (27.36655°N, 91.58034°E, altitude 1760 m) in eastern Bhutan. In this report, a comprehensive overview of the species’ distribution is made. A detailed description of the specimen collected is provided, including phenological details.